Encouraging Improvements in Environmental Reporting - the Role of Award Schemes - Adams, Roger (Ökologisches Wirtschaften - Fachzeitschrift, 1995)
Award schemes can play an important role in encouraging better corporate environmental and financial reporting. The environmental reporting award scheme described below is ad-ministered by the Chartered Association of Certified Accountants (ACCA), a United Kingdom accountancy body which is active in the field of environmental accounting research.